Approaches to supporting lactation and breastfeeding for very preterm infants in the NICU: a qualitative study in three European regions. Issue 6 (30th June 2015) - Bonet, Mercedes; Forcella, Emanuela; Blondel, Béatrice; Draper, Elizabeth S; Agostino, Rocco; Cuttini, Marina; Zeitlin, Jennifer
Abstract : Objectives: To explore differences in approaches to supporting lactation and breastfeeding for very preterm infants in neonatal intensive care units (NICU) in 3 European regions. Design: Qualitative cross-sectional study carried out by means of face-to-face semistructured interviews. Verbatim transcripts were coded using a theoretical framework derived from the literature and supplemented by data-driven concepts and codes. Setting: 4 purposively selected NICUs in each of 3 European regions in 2010 (Ile-de-France in France, Lazio in Italy, and the former Trent region in the UK). Participants: NICU staff members (n=22). Results: Policies and practices for managing mother's own milk for very preterm babies differed between regions, and were much more complex in Ile-de-France than in the Trent or Lazio regions. Staff approaches to mothers to initiate lactation differed by region, with an emphasis on the nutritional and immunological value of human milk in the Trent region and on the 'normalising' effect of breastfeeding on the mother-child relationship in Lazio. French and English staff expressed conflicting opinions about the use of bottles, which was routine in Italy. Italian informants stressed the importance of early maternal milk expression and feeding, but also mentioned discharging infants home before feeding at the breast was established. In Ile-de-France and Trent, successful feeding from the breast was achieved before discharge, although this was seen as a factor that could prolong hospitalisation and discourage continued breastfeeding for some women. Conclusions: Targeted health promotion policies in the NICU are necessary to increase the number of infants receiving their mother's milk and to support mothers with transfer of the infant to the breast. Integrating knowledge about the different approaches to lactation and breastfeeding in European NICUs could improve the relevance of recommendations in multiple cultural settings.